The β-N-Acetylhexosaminidase in the Synthesis of Bioactive Glycans: Protein and Reaction Engineering - Bojarová, Pavla; Kulik, Natalia; Hovorková, Michaela; Slámová, Kristýna; Pelantová, Helena; Křen, Vladimír (Molecules, 2019)
N-Acetylhexosamine oligosaccharides terminated with GalNAc act as selective ligands of galectin-3, a biomedically important human lectin. Their synthesis can be accomplished by β-N-acetylhexosaminidases (EC 3.2.1.52). Advantageously, these enzymes tolerate the presence of functional groups in the substrate molecule, such as the thiourea linker useful for covalent conjugation of glycans to a multivalent carrier, affording glyconjugates. β-N-Acetylhexosaminidases exhibit activity towards both N-acetylglucosamine (GlcNAc) and N-acetylgalactosamine (GalNAc) moieties. A point mutation of active-site amino acid Tyr into other amino acid residues, especially Phe, His, and Asn, has previously been shown to strongly suppress the hydrolytic activity of β-N-acetylhexosaminidases, creating enzymatic synthetic engines. In the present work, we demonstrate that Tyr470 is an important mutation hotspot for altering the ratio of GlcNAcase/GalNAcase activity, resulting in mutant enzymes with varying affinity to GlcNAc/GalNAc substrates. The enzyme selectivity may additionally be manipulated by altering the reaction medium upon changing pH or adding selected organic co-solvents. As a result, we are able to fine-tune the β-N-acetylhexosaminidase affinity and selectivity, resulting in a high-yield production of the functionalized GalNAcβ4GlcNAc disaccharide, a selective ligand of galectin-3.
Keywords: beta-N-acetylhexosaminidasy; Polysaccharides; beta-N-Acetylhexosaminidases; Humans; proteinové inženýrství; molekulární modely; lidé; Hydrogen-Ion Concentration; Protein Engineering; aktivace enzymů; molekulární konformace; Enzyme Activation; vodíková vazba; Kinetics; Molecular Conformation; kinetika; mutace; hydrolýza; Hydrogen Bonding; Mutation; koncentrace vodíkových iontů; polysacharidy; Models, Molecular; Hydrolysis